Isolation and characterization of morphogenetic mutants of Arthrobacter crystallopoietes. - Achberger, E C (1978)
Mutants of Arthrobacter crystallopoietes that exhibited altered ability to undergo the normal sphere-to-rod-to-sphere morphogenetic cycle were isolated. The procedure used to isolate these mutants involved velocity sedimentation in a sterile sucrose gradient to separate morphogenesis-deficient spherical cells from rod-shaped cells capable of normal morphogenesis. Three classes of mutants were obtained: (i) those that cannot form rods, (ii) those that cannot form long rods, and (iii) those that form long rods but exhibit more extensive rudimentary branching than the wild type. The isolation and characterization of these mutants are described, and the use of these mutants in the study of the morphogenetic cycle of arthrobacters is discussed.